2022
DOI: 10.1158/1538-7445.sabcs21-p4-04-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-04-06: Integrative analysis of single-cell transcriptomic and spatial profiles characterized distinct tumor microenvironment phenotypes in hormone receptor positive (HR+) breast cancer

Abstract: Background Clinical trials have shown minimal activity of immune checkpoint blockade (ICB) in HR+ breast cancer. While this is, in part, attributable to low tumor-infiltrating lymphocyte (TIL) levels in HR+ breast cancer, a thorough investigation of the immunologic aspects of the tumor microenvironment (TME) is required to fully understand the limited efficacy of ICB in HR+ disease. We sought to characterize the TME of HR+ breast cancer at single cell resolution using single-cell RNA-seq (scRNA-seq), paired wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Here, we revealed that tumor immunity differed between the high- and low-risk groups defined based on the LMRG signature. Although ER+ BC is generally considered a “cold tumor”, recent genomic, proteomic and single-cell studies have revealed heterogeneity and the existence of an activated immune phenotype in luminal BC with enrichment of TIICs ( 14 , 52 , 69 ). In our findings, low-risk tumors contained significant infiltration of immune cells, including CD8+ T cells and activated NK cells, as well as high MHC-I expression.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we revealed that tumor immunity differed between the high- and low-risk groups defined based on the LMRG signature. Although ER+ BC is generally considered a “cold tumor”, recent genomic, proteomic and single-cell studies have revealed heterogeneity and the existence of an activated immune phenotype in luminal BC with enrichment of TIICs ( 14 , 52 , 69 ). In our findings, low-risk tumors contained significant infiltration of immune cells, including CD8+ T cells and activated NK cells, as well as high MHC-I expression.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor-immune border of "compartmentalized" tumors, cancer cells express HLA-DR, B cells are depleted, while granulocytes (MPO+) are enriched [28]. Intriguingly, spatial distribution of immune cells can also classify hormone receptor-positive BC (HR+ BC), into "cold", "restricted" or "hot" [86].…”
Section: Inter-patient Spatial Heterogeneity: Characterization Of Spa...mentioning
confidence: 99%